Anal sphincter dysfunction in patients treated with primary radiotherapy for anal cancer: a study with the functional lumen imaging probe. (3rd April 2018) - Haas, Susanne; Faaborg, Pia; Liao, Donghua; Laurberg, Søren; Gregersen, Hans; Lundby, Lilly; Christensen, Peter; Krogh, Klaus
Abstract: Background: Sphincter-sparing radiotherapy or chemoradiation are standard treatments for patients with anal cancer. The ultimate treatment goal is full recovery from anal cancer with preserved anorectal function. Unfortunately, long-term survivors often suffer from severe anorectal symptoms. The aim of the present study was to characterize changes in anorectal physiology after radiotherapy for anal cancer. Method: We included 13 patients (10 women, age 63.4 ± 1.9) treated with radiotherapy or chemoradiation for anal cancer and 14 healthy volunteers (9 women, age 61.4 ± 1.5). Symptoms were assessed with scores for fecal incontinence and low anterior resection syndrome. Anorectal physiology was examined with anorectal manometry and the Functional Lumen Imaging Probe. Results: Patients had a median Wexner fecal incontinence score of 5 (0–13) and a median LARS score of 29 (0–39). Compared to healthy volunteers, patients had lower mean (±SE) anal -resting (38 ± 5 vs. 71 ± 6, p  < .001) and -squeeze pressures (76 ± 11 vs. 165 ± 15, p  < .001). Patients also had lower anal yield pressure (15.5 ± 1.3 mmHg vs. 28.0 ± 2.0 mmHg, p  < .001), higher distensibility, and lower resistance to flow (reduced resistance ratio of the anal canal during distension, q  = 5.09, p  < .001). No differences were found in median (range) rectal volumes at first sensation (70.5 (15–131) vs. 57 (18–132) ml, p  > .4), urge (103 (54-176) vs. 90 (32-212), p  > .6) or maximum tolerable volume (173 (86–413) vs. 119.5 (54–269) ml, p  > .10). Conclusion: Patients treated with radiotherapy or chemoradiation for anal cancer have low anal resting and squeeze pressures as well as reduced resistance to distension and flow.